An overview of small aircraft design at Wichita State University - Miller, L. Scott (Kansas State University, 2013)
Wichita State University (WSU) has designed, built, and flown over fifty (50) small and unique aircraft over the last five years. The planes vary in span and weight, respectively, between one to twelve feet and one to twenty-five lbs. Most of the aircraft were designed to meet undergraduate capstone senior design course requirements. Fifteen (15) of the planes utilized autopilot systems and one (1) design explored autonomous cooperative operations (between multiple aircraft for enhanced soaring performance). The presentation will review WSU academic and research experiences and plans/opportunities for the future.
Keywords: Unmanned air vehicles; Wichita State University Aerospace Engineering Department; Curriculum development; Undergraduate course